1978
DOI: 10.1093/nar/5.3.1041
|View full text |Cite
|
Sign up to set email alerts
|

The identification of the tRNA substrates for thesupKtRNA methylase

Abstract: Purified preparations of the tRNA methylase deficient in supK strains of Salmonella typhimurium transfer methyl groups from S-adenosylmethionine (SAM) to at least two tRNA species, an alanine tRNA and a serine tRNA. The identity of the tRNA substrates for this enzyme was determined by a change in the elution position of the methyl-labeled tRNA from BND-cellulose columns before and after aminoacylation with a specific amino acid followed by derivatization of the free primary amino group with phenoxy- or naphtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…This particular problem has been solved by Pope in a different context [16]. We can summarise his results as follows.…”
Section: Bps Dyons In N = 2 Su (3) Yang-mills Theorymentioning
confidence: 94%
See 1 more Smart Citation
“…This particular problem has been solved by Pope in a different context [16]. We can summarise his results as follows.…”
Section: Bps Dyons In N = 2 Su (3) Yang-mills Theorymentioning
confidence: 94%
“…The BPS monopole moduli space for this case is given by R 3 × (R × M)/Z where M is Taub-NUT space [5,14]. The BPS spectrum is then determined by solving the Dirac equation on the Taub-NUT manifold twisted by the tri-holomorphic Killing vector field and we will be able to utilise the results of Pope who studied precisely the same operator in [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the coding specificity of a tRNA can be altered by a change in the anticodon, either by base substitution (for review, see refs. [4][5][6] or by loss ofa base modification (7)(8)(9). In addition to anticodon changes, nucleotide substitutions in other parts of a tRNA molecule can result in suppression by causing attachment of an incorrect amino acid (5,10).…”
Section: Methodsmentioning
confidence: 99%
“…How this change, distant from the anticodon, alters the codon response has not been completely resolved, but a consequent change in the tertiary structure of the molecule has been implicated (13)(14)(15). Other mutational studies (7)(8)(9)(16)(17)(18)(19) also have indicated the importance oftRNA conformation in determining the specificity of codon response.…”
Section: Methodsmentioning
confidence: 99%
“…First, the supK strain of S. typhimurium has two properties: suppression of UGA and a low level of tRNA methyltransferase (10,11,13). To explain this phenomenon, we have suggested that the supK gene encodes RF2 and that its mutant form affects the expression of the methyltransferase (4a).…”
mentioning
confidence: 99%